Comprehensive Comprehensive Analysis of the Implementation of Solid Medical Waste Management Systems in the Community Health Centers (Puskesmas) of Sungai Penuh City - Sofyan, Desmawirdani; Syarifuddin, Hutwan; Maryani, Anis Tatik (Jurnal KESANS : Kesehatan dan Sains, 2026)
Introduction: The management of solid medical waste in primary healthcare facilities remains a critical issue, particularly in Sungai Penuh City, which operates five inpatient health centers serving nearly 100,000 residents. A nearly tenfold increase in waste volume from 2020 to 2023 driven by the surge in single-use PPE during the pandemic, limited availability of autoclaves, licensed incinerators, and cold storage, as well as open burning practices and delayed handover exceeding 48–72 hours high lights the need for a comprehensive assessment. Objective: This study aims to evaluate the current condition of solid medical waste management in the five major health centers and identify gaps in regulatory compliance. Method: A qualitative mixed-method approach was applied through field observations, structured interviews, and document review, validated using source and technique triangulation. Result and Discussion: Findings show that four key stages of waste management remain suboptimal: segregation scored 124 (inadequate), internal collection and transport scored 66 (highly noncompliant), and temporary storage scored 112 (highly noncompliant). In contrast, external transport and treatment scored 114 (highly compliant), though hindered by irregular scheduling. Conclusion: These results underscore the urgency to strengthen infrastructure, regulatory adherence, and scheduled waste transport systems. Future research should assess the effectiveness of eco-friendly technological interventions and competency-based training models to enhance safety and sustainability in medical waste management.